PENGEMBANGAN PERANGKAT PEMBELAJARAN TEMATIK INTEGRATIF SD MELALUI PENDEKATAN SAINTIFIK UNTUK MENUMBUHKAN NILAI KARAKTER - Fine Reffiane; Henry Januar; Husni Wakhyudin (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2016)
Curriculum 2013 is a form of change in education. One of the implementations through integrative thematic learning with scientific approach. Character value of student is a response learners in the moral situation that is manifested in real action through good behavior, honest, responsible, and respectful of others, and other noble character. Device designed to foster learning character values of student. This study aims to (1) develop an integrated thematic learning tools that encourage elementary character values and (2) To obtain the effectiveness of integrative thematic learning with scientific approach to grow the value of character and student learning outcomes. Procedure development using Borgand Gall models include (1) PreliminaryStudy(2) Development (3) Testing. Learning the test subjects in this study were fourth grade students SD Rejosari 3 Semarang. Data collection instrument in this studyachievement test instruments and sheet validation. Analysis of the data used is descriptive analysis of the results of the assessment validator to learning and research instruments, as well as quantitative analysis of observations and comparisons test learners. Validator assessment results obtained average value Syllabus 4.10, RPP 4.09, and LKS 4.15. The results of the calculation, the average value of the study of students at 85. 68% of students have a very good character value and 2% of students have a good character value. Elementaryscience teaching tools through outdoor learning is one alternative that can be used in the elementary school teacher presents the material science to grow the value of character of students.